2023
DOI: 10.1080/19490976.2023.2263207
|View full text |Cite
|
Sign up to set email alerts
|

Progress of linking gut microbiota and musculoskeletal health: casualty, mechanisms, and translational values

Yu Wang,
Yusheng Li,
Lin Bo
et al.

Abstract: The musculoskeletal system is important for balancing metabolic activity and maintaining health. Recent studies have shown that distortions in homeostasis of the intestinal microbiota are correlated with or may even contribute to abnormalities in musculoskeletal system function. Research has also shown that the intestinal flora and its secondary metabolites can impact the musculoskeletal system by regulating various phenomena, such as inflammation and immune and metabolic activities. Most of the existing liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 276 publications
(344 reference statements)
0
3
0
Order By: Relevance
“…(Table 4 ). Owing to their unique advantages, engineered OMVs have garnered substantial attention from researchers, and numerous encouraging preclinical studies have been reported on their use in the past few years 133 .…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…(Table 4 ). Owing to their unique advantages, engineered OMVs have garnered substantial attention from researchers, and numerous encouraging preclinical studies have been reported on their use in the past few years 133 .…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…However, current research and treatments primarily focus on chronic diseases, leaving a dearth of studies investigating whether SCFAs exert similar effects in healthy adults or athletes. Regarding postbiotics, other studies have shown that oral intake of heat-killed Bifidobacterium breve B-3 (HKB-3) resulted in increased grip strength after 2 or 4 weeks and improved distribution of oxidative fibers in the gastrocnemius muscle, ultimately promoting muscle hypertrophy and modification [ 19 ].…”
Section: Microecologics Improve the Function Of Locomotor System And ...mentioning
confidence: 99%
“…Moreover, AMPK can also mediate the AMPK/PGC-1α pathway to regulate mitochondrial biogenesis, providing the necessary energy substrate for ATP synthesis. Many studies have shown that the gut microecosystem can participate in body energy synthesis and utilization via regulating various signaling pathways mediated by AMPK [ 19 , 102 , 103 ]. In an animal experiment, the administration of COSs for 6 weeks significantly increased the expression levels of Sirt1 and AMPK in rat muscle, both of which play important roles in mitochondrial biosynthesis.…”
Section: Promotion Mechanisms Of Microecologics On Exercise Abilitymentioning
confidence: 99%
See 1 more Smart Citation